Transformasi Kebijakan Pemidanaan Dalam Kuhp Nasional: Menuju Sistem Pemidanaan Yang Berkeadilan Dan Humanis - Sri Ismawati; Mega Fitri Hertini; safaruddin Harefa (Simbur Cahaya, 2025)
Indonesia’s penal system has long been dominated by a retributive approach inherited from colonial legal traditions, where imprisonment serves as the primary punishment for criminal offenders. This model has led not only to chronic prison overcrowding but also to the dehumanization of inmates, who still possess fundamental human rights. The newly enacted Indonesian Penal Code (KUHP) marks a significant shift toward a more progressive and humanistic penal paradigm, grounded in the values of Pancasila and the principles of restorative justice. This article aims to normatively analyze the paradigm shift in criminal punishment introduced by the new KUHP and its implications for Indonesia’s penal system, particularly in encouraging the implementation of alternative punishments such as community service, probation, and fines. The study employs a normative legal approach with qualitative analysis of relevant laws, regulations, and legal literature. Findings indicate that the application of alternative sanctions offers a viable solution to prison overcrowding while aligning with the rehabilitative and reintegrative goals of the correctional system. Nonetheless, several challenges remain, including the readiness of law enforcement institutions, infrastructure limitations, and the persistence of a punitive legal culture that views imprisonment as the only legitimate form of punishment. Therefore, a comprehensive implementation strategy is required, involving strong collaboration among government institutions, law enforcement, academia, and civil society to ensure a smooth transition toward a more just, restorative, and humane penal system.